Assessment of Cardio Respiratory Fitness of Trained and Non-Trained Young Adult Males - Limbu, Rekha; Limbu, Nirmala; Khadka, Rita; Subedi, Priza; Limbu, Dilmaya (Journal of Nobel Medical College, 2022)
Background: Cardio respiratory fitness in terms of maximum oxygen uptake (VO2 max) reflects the physical fitness of a person. VO2max determines the capacity of an individual to perform sustained exercise. The present study is to assess and compare the cardiorespiratory fitness in terms of VO2 max between trained and untrained subjects. Materials and Methods: This cross-sectional study was conducted on 30 young adult males undergoing physical training for more than 3 months to join British army and age-sex matched 30 non-trained controls. VO2max was estimated indirectly by following the protocol of Queen’s College Step Test (QCT) method. Results: VO₂ max was found significantly higher in the trained males as compared to non-trained group (68.91± 4.42 vs. 50.31±4.80; p=0.02). On comparison of VO₂ max of our subjects with the standard VO₂ max classification, our trained and non-trained groups fitted into the category of high and average on cardiorespiratory fitness scale respectively. Conclusion: Physical training improves cardio respiratory fitness by increasing VO₂ max.